2014
DOI: 10.1016/j.geomorph.2013.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Gully erosion susceptibility assessment by means of GIS-based logistic regression: A case of Sicily (Italy)

Abstract: This research aims at characterizing susceptibility conditions to gully erosion by means of GIS and multivariate statistical analysis. The study area is a 9.5 km 2 river catchment in central-northern Sicily, where agriculture activities are limited by intense erosion. By means of field surveys and interpretation of aerial images, we prepared a digital map of the spatial distribution of 260 gullies in the study area. In addition, from available thematic maps, a 5 m cell size digital elevation model and field ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
192
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 287 publications
(204 citation statements)
references
References 79 publications
10
192
0
2
Order By: Relevance
“…The NE Hungarian badlands are unique landforms in the Carpathian Basin; therefore, it is quite topical to reveal the recent degradation processes there. High resolution digital elevation models are the essential elements for the majority of the calculations and models referring to watershed analysis (Czigány et al 2013), valley development (Telbisz et al 2012), soil erosion and badland morphology (Conoscenti et al 2008(Conoscenti et al , 2014Lopez Saez et al 2011) that could be combined with several other factors as well (i.e. lithology, land use) for delineating the erosion susceptible areas for instance.…”
Section: Introductionmentioning
confidence: 99%
“…The NE Hungarian badlands are unique landforms in the Carpathian Basin; therefore, it is quite topical to reveal the recent degradation processes there. High resolution digital elevation models are the essential elements for the majority of the calculations and models referring to watershed analysis (Czigány et al 2013), valley development (Telbisz et al 2012), soil erosion and badland morphology (Conoscenti et al 2008(Conoscenti et al , 2014Lopez Saez et al 2011) that could be combined with several other factors as well (i.e. lithology, land use) for delineating the erosion susceptible areas for instance.…”
Section: Introductionmentioning
confidence: 99%
“…It enables the creation of reliable predictive models from explanatory variables (either continuous or discrete). This technique, already used successfully to evaluate several phenomena-e.g., landslide hazard, water erosion, sinkhole susceptibility, human-caused ignition, etc.-evaluates the probability of an event occurrence (P) by estimating the possibility that a case will be classified into one of two mutually exclusive categories as opposed to the other category of the dependent dichotomous variable [54]. In this research, we used logistic regression to establish a functional relationship between the presence or not of fire impact within a plot in a binary-coded manner (1 = high burn severity; 0 = absence or low burn severity) and the set of the independent variables derived from ALS data.…”
Section: Discussionmentioning
confidence: 99%
“…The Hosmer and Lemeshow test is similar to a chi-square test, and it indicates the extent to which the model provides better fit than a null model with no predictors, i.e., how well the model fits the data, as in log-linear modelling. The significance was assessed individually for each independent variable incorporated in the model by means of the Wald test [50,54]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite their lower resolutions compared to UAS imagery, satellite and aerial images as data sources have also been studied for fissure extraction by various researchers [23,[34][35][36][37][38]. Youssef et al [34] demonstrated the use of high-resolution satellite images using QuickBird imagery, acquired on 2 June 2007 (0.61 m spatial resolution), for detailed mapping of recent developments and slope instability hazard zones.…”
Section: Introductionmentioning
confidence: 99%
“…Shruthi et al [37] also investigated the use of object-oriented image analysis to extract erosion features, using a combination of topographic, spectral, shape (geometric) and contextual information obtained from satellite imagery. Conoscenti et al [38] presented a characterization of susceptibility conditions using DEM and aerial images for gully erosion by means of GIS and multivariate statistical analysis. Table 1 summarizes scales, precisions, and data sources of some mentioned scientific analyses.…”
Section: Introductionmentioning
confidence: 99%